2019
DOI: 10.1111/ijac.13432
|View full text |Cite
|
Sign up to set email alerts
|

The fracture properties of metal‐ceramic composites manufactured via stereolithography

Abstract: In this work, metal-ceramic composite parts based on aluminum and alumina were manufactured in a two-stage process. First, silica was printed using a vat photopolymerization technique, followed by a curing and sintering stage, which resulted in ceramic precursors. Subsequently, these samples were subjected to a metal infiltration process to form interpenetrating metal-ceramic composites (IPCs). These composites have attracted considerable attention in the aerospace and defense sector due to the ductility assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…These results can be explained by the fusion of the ceramic particles during the sintering stage (Fig. S2) as reported by Mummareddy et al 44 When comparing the stress-strain profiles of the solid electrodes in the green and sintered state (Fig. 5a, it can be observed that the green sample exhibits a relatively higher ductility than the sintered specimen due the influence of the polymer resin.…”
Section: Tio2supporting
confidence: 80%
“…These results can be explained by the fusion of the ceramic particles during the sintering stage (Fig. S2) as reported by Mummareddy et al 44 When comparing the stress-strain profiles of the solid electrodes in the green and sintered state (Fig. 5a, it can be observed that the green sample exhibits a relatively higher ductility than the sintered specimen due the influence of the polymer resin.…”
Section: Tio2supporting
confidence: 80%
“…The properties of 3D printed ceramics can be controlled and potentially be improved by studying the particle concentration and size distribution in photopolymer resin, and the sintering schedule. [ 62 ]…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
“…[27] The approach demonstrated here uses only a calculated amount of metal and produces lesser waste compared to techniques presented in previous studies., [41,43,45,46,61] Second, the infiltration process utilized for this work is time-independent, that is, the amount of infiltration into the ceramic preform is not influenced by the amount of time the molten metal was molten. For ceramic-metal fabrication techniques like pressureless infiltration [27,30,31] and reactive-metal infiltration [24,62,63] the extent of infiltration is directly proportional to the time the molten metal stayed in contact with the preform. [24,30] Third, the control over the design of individual phase morphologies, achieved utilizing the flexibility of ceramic additive manufacturing, provides us with a tool for the development of new architectural designs that can be tailored to suit different applications.…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Composites with an advanced, interpenetrating (also bi-or co-continuous) microstructure allows for an enhancement of various properties such as stiffness, [4,5] strength, [6] toughness, [7] wear, [8,9] as well as thermal expansion. [4,10] In particular, the possibility to combine and optimize two or more different features simulataneously, e.g., mechanical strength and thermal expansion or thermal/electrical conductivity, [11,12] thus creating multifunctional materials makes interpenetrating composites stand out compared to classical particle or fiber-reinforced MMCs.…”
Section: Introductionmentioning
confidence: 99%